Exploring search behaviour across expertise levels: Graphical vs. form-based interfaces - Russell-Rose, Tony; Svarre, Tanja (Information Research an international electronic journal, 2026)
Introduction. This study explores how graphical and form-based search interfaces influence query reformulation strategies and search performance across two user cohorts: search professionals and master’s students. Method. Using a lab-based user study, participants completed controlled search tasks within the digital health domain, with their interactions analysed in terms of query construction, reformulation tactics, and alignment with expert-crafted gold standard queries. Results. Results reveal distinct patterns between the cohorts, with professionals demonstrating greater precision and efficiency, particularly when using the form-based interface, while students engaged more extensively with the graphical interface, performing more frequent and substantial reformulations. Specification (SPE) and generalisation (GEN) emerged as the most common reformulation strategies, with the graphical interface encouraging broader exploration but also leading to higher occurrences of inappropriate keyword use, particularly among students. Query quality, measured by precision, recall, and F-measure, showed that while form-based systems yielded higher precision, graphical interfaces achieved better recall, offering a balanced trade-off between these metrics. Conclusions. The findings highlight the importance of tailoring search interfaces to meet the needs of different user groups and suggest opportunities for adaptive interface designs that combine the strengths of both systems. Future research should investigate the role of user intentions in query reformulation and the potential for interfaces to provide context-sensitive support.